Ministerial decree no. 344/2017 on amending some provisions of decrees no. 31/1960 concerning visas and 180/1964 = قرار وزاري رقم 344 لسنة 2017 بتعديل بعض أحكام القرارين رقمي 31 لسنة 1960 في شأن التأشيرات و 180 لسنة 1964 - Egypt : Ministry of Finance. The Egyptian Customs Authority (2025)
Ministry of the interior decree no. 344 of the year 2017 on amending some provisions of decrees nos. 31 of the year 1960 concerning visas and 180 of the year 1964 concerning the Implementation of some provisions of law no. 89 of the year 1960 on the foreigners entry to, residence in and departure from the lands of the Arab Republic of Egypt قرارات وزارة الداخلية قرار رقم 344 لسنة 2017 بتعديل بعض أحكام القرارين رقمى 31 لسنة 1960 فى شأن التأشيرات و 180 لسنة 1964 فى شأن تنفيذ بعض أحكام القانون رقم 89 لسنة 1960 بدخول وإقامة الأجانب بأراضى جمهورية مصر العربية والخروج منها